A review on the cracking,baking and leaching processes of rare earth element concentrates - Sadri, Farzaneh; Nazari, Amir Mohammad; Ghahreman, Ahmad (Journal of rare earths, 2017)
Rare earth elements（REE） are a set of seventeen chemical elements in the periodic table, which have been found in a variety classes of minerals in the world. The global demand for REE and their compounds has increased in high-tech applications over the past decades due to their chemical, catalytic, electrical, magnetic, and optical properties. After mining, comminution and ore beneficiation, hydrometallurgical and pyrometallurgical processes are carried out to recover REE compounds. The concentrate cracking is a process wherein the structure of a REE mineral is modified in order to dissolve REE in a weak acid solution. This would be accomplished through various techniques such as alkaline cracking and acid baking. The cracked concentrate is then leached to dissolve REE in a solution and subsequently recover those via neutralization, precipitation or solvent extraction methods. This paper reviewed the cracking and leaching methods applied to REE concentrates to produce an intermediate product for further REE separation.